Adapting to Transformations in Hospital Structure: A Case Study at Manguharjo Lung Specialist Hospital, Madiun - Pratiwi, Ajeng Christiana Putri; Demartoto, Argyo; Murti, Bhisma (Journal of Health Policy and Management, 2025)
Background: Manguharjo Lung Specialist Hospital is a type C hospital in Madiun. Along with global health trends, health needs are increasing and varying. So the Management of Manguharjo Lung Hospital innovated to improve more diverse services by changing the form to a general hospital with a Man, Money, Method, Material, Market approach. The aim of this study was to examine the preparation of a non-pulmonary disease treatment program at the Manguharjo Lung Specialist Hospital, East Java, Indonesia.Subjects and Method: This qualitative study uses a case study approach, involving 4 hospital staff, 3 patients, 3 East Java Health Office officials, and 3 local community leaders. Data sources include interviews and a review of the hospital's strategic development plans and supporting documents.Results: Five themes emerged: (1) Opportunities for conversion, supported by strategic location, adequate resources, and community demand for non-pulmonary services; (2) Supporting factors, including skilled human resources and the potential for increased hospital income; (3) Public perception, where the hospital is still viewed primarily as a lung service facility, deterring broader usage; (4) Obstacles, particularly lack of approval from the East Java Health Office; (5) Efforts, such as opening non-lung services and preparing human resources and facilities.Conclusion: Manguharjo Lung Specialist Hospital has significant potential to transition into a general hospital due to strong supporting factors like skilled personnel. However, challenges like public perception and institutional approval must be addressed.